STRATEGI KOLABORASI BRANCHLESS BANK SYARIAH DI TENGAH PERSAINGAN DAN PERUBAHAN TEKNOLOGI - Adhitya Ginanjar (Faculty of Economics and Business, 2015)
Implementing branchless banking (financial services in financial inclusion) in sharia banking industry shows that sharia banking still needs government and society support. Less amount of sharia banking infrastructure is not likely contribute to asset growth. Limited quality and quantity of sharia banking human resources has not maximize widely and deeply sharia market segment. Strategy of sharia banking collaboration with micro enterprise has engaged normally however, it has not taken over conventional banking.